Analysis of transient processes in levitation electromechanical systems including effects of magnetic potential hole. Issue 1 (February 2021) - Czaban, A; Łukasik, Z; Lis, M; Szafraniec, A
Abstract: A mathematical model of a dynamic system including superconducting electric circuits and effects of the magnetic potential hole is presented. Motion transmission of the magnetic cushion rapid train, known as maglev train, which uses natural magnetic static levitation, is modelled on this basis. Starting from the model, transient electromechanical processes in an integrated dynamic system are analysed. The model is presented as a system of non-linear differential equations in the normal Cauchy's form. The equations are integrated by means of explicit numerical methods. Results of computer simulations are illustrated as graphs whose behaviour is analysed.